Desempeño laboral de los empleados del Gad Parroquial Ricaurte - Herrera Calderon, Wilson David (2020)
The Ricaurte Parochial Decentralized Autonomous Government has the primary function of being the legal representative and permanent communicator between the local and provincial jurisdictions. It proceeds through the organization, guidance, advice, training, technical support, application of standards or policies, for the constant development of society. The president of the institution is Mr. Alfonso Rosero Gómez. Companies try to do everything possible to maintain a high level of performance in their workers because this contributes to achieve the objectives that have been previously proposed. Work performance is related to the skills that a person has and the effort they make to demonstrate their skills and abilities in the performance of their work, however the organization presents certain problems, among them it can be identified that employees do not perform their activities in an efficient way damaging the proper functioning of the institution.